The Influence of Principal’s Leadership and School Organizational Climate on Teacher’s Job Satisfaction - Susilawati, Susilawati; Ahyani, Nur; Mahasir, Mahasir (Graduate Program Magister Manajemen Pendidikan, 2024)
The objectives of this study: 1) to determine the influence of the principal’s leadership on teacher’s job satisfaction; 2) to determine the effect of school organizational climate on teacher’s job satisfaction; and 3) to find out jointly the influence of the principal’s leadership and school organizational climate on teacher’s job satisfaction. This research was carried out at SD Negeri Gugus 2, Teluk Gelam District, Ogan Komering Ilir Regency with a total research sample was 71 teachers. Data collection techniques were carried out through observation, documentation studies, and distribution questionnaires. The validity test uses construct validity, while the reliability test uses Cronbach’s Alpha. Linearity Test and Normality Test. The results of this research are: 1) there is a partially significant influence between leadership on teacher’s job satisfaction; 2) there is a partially significant influence between organizational climate on teacher’s job satisfaction; and 3) there is a simultaneous influence between leadership and organizational climate on teacher’s job satisfaction. This study recommends all schools in Indonesia should have good principal’s leadership and organizational climate, in order to have good teacher’s job satisfaction.